REFORMASI AKUNTANSI : MENGAPA ACCRUAL BASIS LEBIH BAIK ? - Riza Praditha; Kartini Kartini; Henni Mande (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
The purpose of writing this article is to explore and understand more deeply what kind of Accrual Basis and Cash Basis and what is behind the change of Cash Basis method to Accrual Basis on public sector organization and why Accrual Basis is better than Cash Basis. This paper is a literature study using Qualitative Descriptive Comparative method. The results found that the existence of Basis Cash changes to Accrual Basis backed by the condition of accounting information. Accrual Basis is considered more multiply because it is able to present more transparent and accountable information on financial statements compared to Cash Basis so as to reduce the potential for fraud.